Nutritional Quality and Total Bacterial Colonies in Goat Milk Yoghurt-Based Ice Cream with the Addition of Salak Pondoh Puree (Salacca Edulis Reinw - Batubara, Wan Ramadhani; Nurzainah Ginting; Achmad Sadeli (Jurnal Peternakan Integratif, 2025)
Ice cream is one of products that is widely favored by various groups of people. This study aims to determine and evaluate organoleptic and nutritional properties and determine the total number of bacterial colonies in goat milk yogurt-based ice cream with different concentrations with the addition of salak pondoh puree using a Completely Randomized Design (CRD) with 4 levels of treatment with 5 replications, namely (P): (0 mL; 150 mL; 300 mL; 450 mL). The parameters analyzed included fat content, protein content, total bacterial colonies, organoleptic color, aroma, texture, and taste. The results showed that the addition of salak pondoh puree to goat milk yoghurt-based ice cream can increase organoleptic values in the form of color, aroma, texture, and also color so that it is preferred by panelists. The addition of salak pondoh puree provides fat content, protein content, and total bacterial colonies in goat milk yogurt. In conclusion the addition of salak pondoh puree to goat milk yoghurt-based ice cream is accordance with the standards so that it is suitable for consumption.